PILOCYTIC ASTROCYTOMA: A CASE OF NOT SO BENIGN INTRACRANIAL HYPERTENSION. Issue 11 (14th October 2015) - Appleton, Jason Philip; Hayton, Tom; Williams, Adrian
Abstract : Idiopathic intracranial hypertension (IIH) is a condition of raised CSF pressure without any apparent structural lesion or problem with venous drainage. We present a lady who was initially diagnosed with IIH, but was later found to have an unusual brain tumour. A 30 year old lady presented in 2012 with a three month history of headaches, nausea and vomiting, two weeks of blurred vision and one week of double vision on looking left. Visual acuity was 6/6 on the right and 6/9 on the left with a left relative afferent pupillary defect, bilateral papilloedema and left lateral rectus palsy. MRI showed ventriculomegaly. Lumbar puncture revealed normal constituents with an opening pressure of 60 cm H2 O. In the absence of a space occupying lesion or venous occlusion a diagnosis of IIH was made. A ventriculoperitoneal shunt was inserted and she was discharged but didn't attend follow-up. She re-presented in May 2014 with headaches and intermittent left arm and leg numbness. An MRI revealed widespread CSF pathway infiltration, leptomeningeal enhancement, tonsillar descent and an extensive cervical syrinx. She underwent posterior fossa decompression and biopsy, which was histologically confirmed as pilocytic astrocytoma. Ventriculomegaly is not a feature of IIH. This case illustrates the wide differential of raised CSF pressure and that careful assessment of brain imaging and CSF constituents is required prior to making what is, in effect, a diagnosis of exclusion.